Academic Performance Assessment of Students in Higher Education Institution in Nepal: Perspectives of Faculty Members and Students - Baruwal, Hira Bahadur (Academia Journal of Humanities & Social Sciences, 2025)
This paper aims to explore the challenges of assessing student performance from the perspectives of faculty members and students. Student performance is evaluated through formative, summative, and diagnostic assessments during the academic session. A phenomenological research design was employed, using survey questionnaires, interviews, and focus group discussions with non-teaching staff, faculty members, and students of Bachelor Level and Master Level at Myagdi Multiple Campus (MMC), Beni Bazaar, Nepal. The study is grounded in Bloom’s taxonomy, which helps educators specify learning outcomes and evaluate student learning at various cognitive levels. The findings of the study suggest that dual-language testing can be a valuable strategy to enhance student performance and academic outcomes. This study offers insights for educators and policymakers to improve assessment practices and support student success in higher education. Finally, the study concludes that using a dual-language test format enables students to grasp questions more easily, resulting in more accurate answers and improved exam results.